An integrated approach for data security in vehicle diagnostics over internet protocol and software update over the air. (October 2018) - Mayilsamy, Kathiresh; Ramachandran, Neelaveni; Sunder Raj, Vismitha
Abstract: An integrated approach that uses a combination of cryptography and steganography to enhance the data security in automotive applications is proposed in this paper. In this method, the data is encrypted using the modified RSA cryptographic algorithm and the encrypted data is embedded along the edges of the image using Least Significant Bit (LSB) technique. The edges are detected using fuzzy logic approach. This integrated approach is proposed mainly for Diagnostics over Internet Protocol (DoIP) and Software Update over the Air (SOTA) as they involve exchange of highly sensitive data. In addition, the authenticity of the source of software update is verified using Hash Algorithm in SOTA. The proposed method is implemented in MATLAB with Python as back-end platform and the data integrity is validated against various attempts to hack the data using online simulators.